Letter to John Barrow, Esq. on the subject of the polar expedition, or, The reviewer reviewed [electronic resource] - Ross, John, Sir, 1777-1856; Barrow, John, Sir, 1764-1848. (London : James Ridgeway ., 1819)
Signed: A friend to the Navy. Attributed to Sir John Ross--National Union Catalog pre-1956 imprints. '"There thou might'st behold the great image of authority -a Dog's obey' d in office."--Lear.' Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44